The life and work of Innocent, the archbishop of Kamchatka, the Kuriles and the Aleutian Islands and later the metropolitan of Moscow [electronic resource]. - Barsukov, I. P. (Ivan Platonovich) ([San Francisco? : s.n., 1894)
Cover title. Compiled from the book by I.P. Barsukov--National Union Catalogue pre-1956 imprints. "Translated from the Russian and printed for distribution among the people by request of the most Reverend Bishop Nicholas"--T.p. verso. "San Francisco August 26th 1797 -September 7th 1897." Electronic reproduction. Mode of access: Internet. 44